A case of complete albinism in the catfish Cambeva guareiensis (Siluriformes: Trichomycteridae) - Azevedo-Santos, Valter M. [UNESP]; Pelicice, Fernando M.; Sazima, Ivan; Henry, Raoul [UNESP] (Revista Biota Neotropica, 2020)
Albinism has been recorded in Neotropical freshwater fishes, mostly for nocturnal or cryptobiotic species. We report herein a case of albinism in the catfish Cambeva guareiensis (Trichomycteridae) from the Guarei River basin, Upper Parana River basin, southeastern Brazil. The albino fish was caught with seven individuals with typical color pattern of the species. The features of the albino fish in life and shortly after preservation are described and illustrated.
Keywords: Albinism; color anomaly; fish; Guarei River basin; Neotropical region; Paranapanema River basin